FORMATION OF VALEOLOGICAL KNOWLEDGE OF YOUNGER STUDENTS THROUGH PHYSICAL EDUCATION (Physical Culture and Sport: Scientific Perspective, 2025)
The article explores the theoretical and methodological foundations of forming valeological knowledge in younger students through physical education. Emphasis is placed on the importance of valeological education for fostering a conscious attitude toward health, developing health-preserving competencies, promoting physical activity, and ensuring students' awareness of the fundamentals of a healthy lifestyle.An analysis of the organizational forms of physical education aimed at developing valeological knowledge in younger students has been conducted, including physical education lessons and health-promoting activities within the school day. The methods and means of such activities that integrate valeological knowledge into children's motor activities are described. Special attention is given to the use of health-preserving technologies, active games, physical exercises, hardening techniques, breathing exercises, and other means that contribute to the development of practical skills for maintaining health.Effective pedagogical approaches to forming valeological competence have been identified, including activity-based, competency-based, and integrative approaches, which ensure the combination of theoretical knowledge with practical activities, promote the development of reflection, and encourage a conscious attitude toward personal health. Special attention is paid to approaches that support the formation of valeological competence.It is emphasized that the systematic integration of the valeological component into physical education creates optimal conditions for fostering motivation for a healthy lifestyle among younger students. Prospects for further research are outlined in the direction of improving the methodology of valeological education, which will enhance the effectiveness of physical education and facilitate the integration of valeological knowledge into the primary education curriculum.
Keywords: valeological education; physical education; health-preserving competence; valeological knowledge; healthy lifestyle; younger students